Sulfur-doped molybdenum ditelluride nanosheet as well as preparation method and application thereof

By soaking molybdenum ditelluride nanosheets in ammonium sulfide solution, sulfur ions are embedded in the lattice structure of molybdenum ditelluride to form N-type doping, the existing molybdenum ditelluride nanosheet memristor resistance is solved. The problem of poor variable performance achieves better electrical performance and lower energy consumption.

CN119465407AInactive Publication Date: 2025-02-18SICHUAN NORMAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411193565.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing molybdenum ditelluride nanosheet memristor has poor resistance performance and requires a simple and effective doping method to improve its performance.

Method used

By soaking the molybdenum ditelluride nanosheets in an ammonium sulfide solution, sulfur ions are embedded in the lattice structure of molybdenum ditelluride to form an N-type doping, which significantly improves its electrical properties.

Benefits of technology

This method does not require high temperature and high pressure environments or complex physical bombardment, has low energy consumption, and the N-type doping formed significantly improves the resistance of molybdenum ditelluride nanosheets, making it more suitable for the preparation of memristor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465407A_ABST
    Figure CN119465407A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-doped molybdenum ditelluride nanosheet as well as a preparation method and application thereof, and belongs to the technical field of nano materials and components. The preparation method comprises the steps that a catalyst and a molybdenum source are mixed and placed in an ark, then a substrate is placed above the ark, and a pretreated molybdenum source is obtained; a tellurium source is also placed in the ark, then the tellurium source and the pretreated molybdenum source are placed in the double-temperature-zone tubular furnace, the tellurium source is placed on the upstream, the pretreated molybdenum source is placed on the downstream, a growth reaction is carried out, heat preservation is carried out, and molybdenum ditelluride nanosheets are obtained; and soaking the molybdenum ditelluride nanosheet in an ammonium sulfide solution, taking out the molybdenum ditelluride nanosheet, washing with water, and drying to obtain the molybdenum ditelluride nanosheet. The invention also discloses the sulfur-doped molybdenum ditelluride nanosheet and an application of the sulfur-doped molybdenum ditelluride nanosheet in preparation of a memristor device. The molybdenum ditelluride nanosheet generated by ammonium sulfide etching chemical vapor deposition realizes simple sulfur doping treatment of molybdenum ditelluride, the sulfur-doped modified molybdenum ditelluride can be used for preparing memristor devices, a foundation is laid for subsequent neuromorphic application, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano materials and components, and specifically relates to a sulfur-doped molybdenum ditelluride nanosheet and a preparation method and application thereof. Background Art

[0002] With the continuous advancement of the times and technology, computer processors have undergone many reforms, from field-effect transistors to integrated circuits and now, a new generation of memory, "memristors", has begun to be deeply studied. Memristors are nonlinear resistors with memory functions, belonging to the fourth category of basic circuit elements. Different from traditional resistors, capacitors and inductors, memristors can "remember" the charge passing through after power failure, so they can store information in circuits and have broad application prospects.

[0003] The resistance change capability of a memristor is referred to as the resistive switching characteristic. This characteristic is reflected in the fact that when a memristor is subjected to an external voltage, its resistance state will be adjusted accordingly, giving the memristor the ability to store multiple resistance states. Under the stimulation of a DC voltage, the measured current-voltage (IV) relationship curve will show a phenomenon called hysteresis. Based on the characteristic differences of the IV curve, the resistive switching type can be mainly divided into two categories: digital resistive switching memristors and analog resistive switching memristors. The characteristic of digital resistive switching memristors is that their resistance value will suddenly change under certain conditions, usually showing a significant order of magnitude difference between the high resistance state and the low resistance state; in contrast, the resistance change of analog resistive switching memristors is more gradual, and as the current gradually changes, its resistance value will also change continuously and tunably, allowing the device to have a series of finely adjustable intermediate states. This resistive switching characteristic is highly similar to the functional mechanism of synapses in biological nervous systems. Therefore, memristors with analog resistive switching behavior are regarded as a potential tool for simulating the complex behavior patterns of biological synapses.

[0004] The existing MoTe (2H phase) nanosheet memristors have poor resistive switching performance. Doping is an effective strategy to adjust their performance for practical applications. There are two basic doping methods in semiconductor materials, namely N-type doping and P-type doping. Common doping methods mainly include hydrothermal method and in-situ conversion method. The hydrothermal method has relatively harsh reaction conditions, requires a high temperature and high pressure environment, and consumes a lot of energy. The in-situ conversion method also requires high temperature reaction conditions, and the doping degree and uniformity may be affected by the morphology and structure of the precursor. How to use a simple method to dope MoTe to achieve modification so that it has better resistive switching performance is one of the unresolved issues. Summary of the invention

[0005] The problem to be solved by the present invention is to provide a sulfur-doped molybdenum ditelluride nanosheet and a preparation method and application thereof, so as to solve the problem of poor resistive switching performance of molybdenum ditelluride.

[0006] The technical solution adopted to solve the technical problem is to provide a method for preparing sulfur-doped molybdenum ditelluride nanosheets, comprising the following steps:

[0007] (1) Mixing the catalyst and the molybdenum source and placing them in an ark, and then placing the substrate on top of the ark to obtain a pretreated molybdenum source;

[0008] (2) placing a tellurium source in the ark, and then placing the tellurium source and the pretreated molybdenum source in a double-temperature zone tubular furnace, with the tellurium source placed upstream and the pretreated molybdenum source placed downstream for growth reaction and heat preservation, to obtain molybdenum ditelluride nanosheets;

[0009] (3) Soaking the molybdenum ditelluride nanosheets in an ammonium sulfide solution, taking them out, washing them with water, and drying them to obtain sulfur-doped molybdenum ditelluride nanosheets.

[0010] The beneficial effects of the above technical solution of the present invention are as follows: ammonium sulfide is composed of sulfide ions and ammonium ions, and the ammonium ditelluride nanosheets generated by chemical vapor deposition (CVD) can be etched with ammonium sulfide to achieve simple doping treatment of molybdenum ditelluride; the sulfide ions in the ammonium sulfide solution can naturally penetrate and embed into the lattice structure of the molybdenum ditelluride nanosheets due to their unique chemical activity, and this process does not require complex physical bombardment or high-energy chemical treatment, thereby greatly reducing the energy consumption and environmental pollution in the doping process. More importantly, this embedding method forms N-type doping, that is, the sulfide ions act as electron donors, increasing the free electron concentration in the material, thereby significantly improving the electrical properties of the molybdenum ditelluride nanosheets; after testing, it has better resistive switching performance than undoped molybdenum ditelluride, and can be used for the preparation of memristor devices.

[0011] Preferably, the catalyst is sodium chloride or potassium chloride; the substrate is a SiO2 / Si substrate; the molybdenum source is molybdenum trioxide; and the tellurium source is tellurium powder.

[0012] The beneficial effect of the above technical solution adopted in the present invention is: sodium chloride or potassium chloride is selected as a catalyst. These metal chlorides have a lower melting point and higher activity, which can reduce the melting point of the molybdenum source and assist in the better growth of molybdenum ditelluride.

[0013] More preferably, the catalyst is potassium chloride.

[0014] Preferably, the mass ratio of the tellurium source to the molybdenum source is 1:0.04-0.06.

[0015] More preferably, the mass ratio of the molybdenum source to the catalyst is 0.6 to 0.9:1.

[0016] Preferably, the carrier gas used in the dual-temperature zone tubular furnace in step (2) is a mixture of argon and hydrogen; the volume concentration of argon is 88-92%, and the volume concentration of hydrogen is 8-12%; the carrier gas flow rate is 18-22 sccm.

[0017] More preferably, the carrier gas used in the dual-temperature zone tubular furnace in step (2) is a mixture of argon and hydrogen; the volume concentration of argon is 90%, and the volume concentration of hydrogen is 10%; the carrier gas flow rate is 20 sccm.

[0018] Preferably, in step (2), the heating temperature of the tellurium source is 550-650°C; the heating temperature of the pretreated molybdenum source is 650-750°C; the growth reaction time is 30-40 minutes; and the insulation time is 15-25 minutes.

[0019] The beneficial effects of the above technical solution adopted in the present invention are as follows: the upstream tellurium source heating temperature is 550-650°C, which is the evaporation temperature of the tellurium source, and the downstream pre-treated molybdenum source heating temperature is 650-750°C, which is the reaction generation temperature of molybdenum ditelluride; since the diffusion direction of the tubular furnace gas is from upstream to downstream, within its temperature range, tellurium and molybdenum react chemically on the surface of the downstream silicon wafer to form a solid deposit of molybdenum ditelluride.

[0020] More preferably, in step (2), the heating temperature of the tellurium source is 600° C.; the heating temperature of the pretreated molybdenum source is 700° C.; the growth reaction time is 35 min; and the holding time is 20 min.

[0021] Preferably, the mass percentage concentration of the ammonium sulfide solution in step (3) is 18-22%, the soaking time is 10-20 minutes, and the drying temperature is 45-55° C., and the drying time is 1.5-2.5 minutes.

[0022] More preferably, the mass percentage concentration of the ammonium sulfide solution in step (3) is 20%, the immersion time is 15 minutes, and the drying temperature is 50° C., and the drying time is 2 minutes.

[0023] More preferably, the water washing conditions in step (3) are: washing with deionized water 3 times.

[0024] The present invention also provides sulfur-doped molybdenum ditelluride nanosheets prepared by the above preparation method.

[0025] The present invention also provides the use of the sulfur-doped molybdenum ditelluride nanosheets in preparing a memristor device.

[0026] Preferably, the use of sulfur-doped molybdenum ditelluride nanosheets in preparing a memristor device comprises the following steps:

[0027] The sulfur-doped molybdenum ditelluride nanosheets are placed on a coating machine, and 1 to 2 drops of photoresist are added to the surface of the substrate, and the coating is performed twice, and the substrate is dried for use; a photolithography machine is used to perform photolithography, exposure and development on both ends of the sulfur-doped molybdenum ditelluride nanosheets, and the nanosheets are taken out and dried; the dried sulfur-doped molybdenum ditelluride nanosheets are placed on the stage of a sputtering instrument and the height of the stage is adjusted, and a high-purity Au target is used for sputtering 2 to 3 times, each time for 15 to 20 seconds; the nanosheets are then soaked in acetone for 8 to 10 minutes, washed with water, ultrasonicated, and dried to obtain an Au / S-MoTe2 / Au memristor device.

[0028] More preferably, the two coating steps include the following steps: coating at 400-600 r / min for 5-15 s, and then coating at 1800-2200 r / min for 25-35 s; exposure time is 10-20 s; and development time is 0.5-1.5 min.

[0029] The present invention has the following beneficial effects:

[0030] (1) The present invention significantly improves the resistive switching performance of molybdenum ditelluride, which originally has a small window value, by sulfur doping. Molybdenum ditelluride modified by sulfur doping can be well used to prepare memristor devices, laying a foundation for subsequent neuromorphic applications and having good application prospects.

[0031] (2) The present invention uses ammonium sulfide to etch the molybdenum ditelluride nanosheets generated by chemical vapor deposition, which can achieve simple sulfur doping treatment of molybdenum ditelluride; the sulfur ions in the ammonium sulfide solution penetrate and embed into the lattice structure of the molybdenum ditelluride nanosheets. This process does not require complex physical bombardment or high-energy chemical treatment, thereby greatly reducing energy consumption and environmental pollution during the doping process. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 An optical microscope image of the Au / S-MoTe2 / Au memristor device prepared in Example 1;

[0033] Figure 2 The EDS characterization diagram of the sulfur-doped molybdenum ditelluride nanosheets prepared in Example 1; wherein (a) is an element distribution diagram; (b) is an element quantitative analysis diagram;

[0034] Figure 3 This is an IV test diagram of the Au / MoTe2 / Au memristor device prepared in Comparative Example 1;

[0035] Figure 4 This is an IV test diagram of the Au / S-MoTe2 / Au memristor device prepared in Example 1;

[0036] Figure 5This is a diagram of the simulated resistance switching performance of the Au / S-MoTe2 / Au memristor device prepared in Example 1 under positive voltage scanning;

[0037] Figure 6 This is a current enhancement response diagram of the Au / S-MoTe2 / Au memristor device prepared in Example 1 under a positive pulse voltage;

[0038] Figure 7 This is the current inhibition response diagram of the Au / S-MoTe2 / Au memristor device prepared in Example 1 under a negative pulse voltage. DETAILED DESCRIPTION

[0039] The features and performance of the present invention are further described in detail below in conjunction with embodiments.

[0040] Example 1

[0041] A method for preparing sulfur-doped molybdenum ditelluride nanosheets comprises the following steps:

[0042] (1) Weigh 0.015 g of molybdenum trioxide and 0.02 g of potassium chloride, mix and place in an ark, then place a SiO2 / Si substrate on top of the ark to obtain a pretreated molybdenum source;

[0043] (2) Weigh 0.25 g of tellurium powder and place it in an ark. Then place the tellurium powder and the pretreated molybdenum source in a double-zone tubular furnace, and use a mixture of argon with a volume concentration of 90% and hydrogen with a volume concentration of 10% as a carrier gas at a carrier gas flow rate of 20 sccm; the tellurium powder is placed upstream of the double-zone tubular furnace and heated to 600° C., the pretreated molybdenum source is placed downstream of the double-zone tubular furnace and 17 cm away from the tellurium powder, heated to 700° C., and the growth reaction is carried out for 35 minutes and kept warm for 20 minutes, and then the furnace is naturally cooled to room temperature to obtain molybdenum ditelluride nanosheets;

[0044] (3) The molybdenum ditelluride nanosheets were immersed in a 20% by mass concentration ammonium sulfide solution for 15 minutes, taken out, washed with deionized water for 3 times, and then placed on a drying table at 50° C. for 2 minutes to obtain sulfur-doped molybdenum ditelluride nanosheets.

[0045] This embodiment also includes sulfur-doped molybdenum ditelluride nanosheets prepared by the above method.

[0046] The application of the sulfur-doped molybdenum ditelluride nanosheets prepared in this embodiment in the preparation of Au / S-MoTe2 / Au memristor devices comprises the following steps:

[0047] The sulfur-doped molybdenum ditelluride nanosheets were placed on a coating machine, and 1 to 2 drops of photoresist were added to the surface of the substrate. The coating was spread at 500 r / min for 10 seconds, and then at 2000 r / min for 30 seconds, and dried at 50°C for 1 minute for use; a photolithography machine was used to photolithograph and expose the two ends of the sulfur-doped molybdenum ditelluride nanosheets for 15 seconds and immersed in a developer for 1 minute, and then taken out and dried at 50°C for 2 minutes; the dried sulfur-doped molybdenum ditelluride nanosheets were placed on the stage of a sputtering instrument and the height of the stage was adjusted, and a high-purity Au target was used for sputtering twice, each time for 20 seconds; then it was soaked in acetone for 10 minutes, washed with deionized water, ultrasonicated, and dried to obtain an Au / S-MoTe2 / Au memristor device.

[0048] Example 2

[0049] A method for preparing sulfur-doped molybdenum ditelluride nanosheets comprises the following steps:

[0050] (1) Weigh 0.012 g of molybdenum trioxide and 0.02 g of potassium chloride, mix and place in an ark, and then place a SiO2 / Si substrate on top of the ark to obtain a pretreated molybdenum source;

[0051] (2) Weigh 0.3 g of tellurium powder and place it in an ark. Then place the tellurium powder and the pretreated molybdenum source in a double-zone tubular furnace, and use a mixture of argon with a volume concentration of 88% and hydrogen with a volume concentration of 12% as a carrier gas at a carrier gas flow rate of 18 sccm; the tellurium powder is placed upstream of the double-zone tubular furnace and heated to 550° C., the pretreated molybdenum source is placed downstream of the double-zone tubular furnace and 17 cm away from the tellurium powder, heated to 650° C., and a growth reaction is carried out for 40 minutes and kept warm for 15 minutes, and then the furnace is naturally cooled to room temperature to obtain molybdenum ditelluride nanosheets;

[0052] (3) Soaking the molybdenum ditelluride nanosheets in an ammonium sulfide solution with a mass percentage concentration of 18% for 10 minutes, taking them out, washing them with deionized water for 3 times, and then drying them on a drying table at 45° C. for 2.5 minutes to obtain sulfur-doped molybdenum ditelluride nanosheets.

[0053] This embodiment also includes sulfur-doped molybdenum ditelluride nanosheets prepared by the above method.

[0054] The application of the sulfur-doped molybdenum ditelluride nanosheets prepared in this embodiment in the preparation of Au / S-MoTe2 / Au memristor devices comprises the following steps:

[0055] The sulfur-doped molybdenum ditelluride nanosheets were placed on a coating machine, and 1 to 2 drops of photoresist were added to the surface of the substrate. The coating was spread at 400 r / min for 15 seconds, and then at 2200 r / min for 25 seconds, and dried at 50°C for 1 minute for use; a photolithography machine was used to photolithograph and expose the two ends of the sulfur-doped molybdenum ditelluride nanosheets for 10 seconds and immersed in a developer for 0.5 minutes, and then taken out and dried at 50°C for 2 minutes; the dried sulfur-doped molybdenum ditelluride nanosheets were placed on the stage of a sputtering instrument and the height of the stage was adjusted, and a high-purity Au target was used for sputtering twice, each time for 20 seconds; then it was soaked in acetone for 10 minutes, washed with deionized water, ultrasonicated, and dried to obtain an Au / S-MoTe2 / Au memristor device.

[0056] Example 3

[0057] A method for preparing sulfur-doped molybdenum ditelluride nanosheets comprises the following steps:

[0058] (1) Weigh 0.018 g of molybdenum trioxide and 0.02 g of potassium chloride, mix and place in an ark, then place a SiO2 / Si substrate on top of the ark to obtain a pretreated molybdenum source;

[0059] (2) Weigh 0.3 g of tellurium powder and place it in an ark. Then place the tellurium powder and the pretreated molybdenum source in a double-zone tubular furnace, and use a mixture of argon with a volume concentration of 92% and hydrogen with a volume concentration of 8% as a carrier gas at a carrier gas flow rate of 22 sccm. The tellurium powder is placed upstream of the double-zone tubular furnace and heated to 650° C. The pretreated molybdenum source is placed downstream of the double-zone tubular furnace and 17 cm away from the tellurium powder, heated to 750° C., and a growth reaction is carried out for 30 minutes and kept warm for 25 minutes. Then the furnace is naturally cooled to room temperature to obtain molybdenum ditelluride nanosheets.

[0060] (3) Soaking the molybdenum ditelluride nanosheets in a 22% by mass ammonium sulfide solution for 20 minutes, taking them out, washing them three times with deionized water, and then drying them on a drying table at 55° C. for 1.5 minutes to obtain sulfur-doped molybdenum ditelluride nanosheets.

[0061] This embodiment also includes sulfur-doped molybdenum ditelluride nanosheets prepared by the above method.

[0062] The application of the sulfur-doped molybdenum ditelluride nanosheets prepared in this embodiment in the preparation of Au / S-MoTe2 / Au memristor devices comprises the following steps:

[0063] The sulfur-doped molybdenum ditelluride nanosheets were placed on a coating machine, and 1 to 2 drops of photoresist were added to the surface of the substrate. The coating was spread at 600 r / min for 5 seconds, and then at 1800 r / min for 35 seconds, and dried at 50°C for 1 minute for use; a photolithography machine was used to photolithograph and expose the two ends of the sulfur-doped molybdenum ditelluride nanosheets for 20 seconds, and the nanosheets were immersed in a developer for 1.5 minutes, and then taken out and dried at 50°C for 2 minutes; the dried sulfur-doped molybdenum ditelluride nanosheets were placed on the stage of a sputtering instrument and the height of the stage was adjusted, and a high-purity Au target was used for sputtering twice, each time for 20 seconds; the nanosheets were then soaked in acetone for 10 minutes, washed with deionized water, ultrasonicated, and dried to obtain an Au / S-MoTe2 / Au memristor device.

[0064] Comparative Example 1

[0065] A method for preparing molybdenum ditelluride nanosheets comprises the following steps:

[0066] (1) Weigh 0.015 g of molybdenum trioxide and 0.02 g of potassium chloride, mix and place in an ark, then place a SiO2 / Si substrate on top of the ark to obtain a pretreated molybdenum source;

[0067] (2) Weigh 0.25 g of tellurium powder and place it in an ark. Then place the tellurium powder and the pretreated molybdenum source in a double-zone tubular furnace, and use a mixture of argon with a volume concentration of 90% and hydrogen with a volume concentration of 10% as a carrier gas at a carrier gas flow rate of 20 sccm. The tellurium powder is placed upstream of the double-zone tubular furnace and heated to 600°C. The pretreated molybdenum source is placed downstream of the double-zone tubular furnace and 17 cm away from the tellurium powder, heated to 700°C, and the growth reaction is carried out for 35 minutes and kept warm for 20 minutes. Then the furnace is naturally cooled to room temperature to obtain molybdenum ditelluride nanosheets.

[0068] This comparative example also includes molybdenum ditelluride nanosheets prepared by the above method.

[0069] In this comparative example, the application steps of molybdenum ditelluride nanosheets in preparing Au / MoTe2 / Au memristor devices are the same as those in Example 1.

[0070] Experimental example

[0071] 1. The sulfur-doped molybdenum ditelluride nanosheets and the Au / S-MoTe2 / Au memristor device prepared therefrom in Example 1 were structurally analyzed. Figures 1-2 As shown. Figure 1 It can be seen from the figure that the Au / S-MoTe2 / Au memristor device prepared by sulfur-doped molybdenum ditelluride of the present invention presents a two-dimensional layered structure. Figure 2 It can be seen that the sulfur element has an atomic ratio of 3.53% in the sulfur-doped molybdenum ditelluride of the present invention and is uniformly distributed, indicating that the sulfur is successfully doped and has a good distribution state.

[0072] 2. The performance of the memristor devices obtained in Example 1 and Comparative Example 1 was measured. The results are as follows: Figures 3 to 7 shown.

[0073] Figure 3 This is the IV test diagram of the Au / MoTe2 / Au memristor device prepared in Comparative Example 1 at ±20V. It can be seen that the original (undoped with sulfur) molybdenum ditelluride device needs to be under a large voltage to have a little resistance switching performance, and the window value is small, indicating that the undoped sulfur molybdenum ditelluride device has poor resistance switching performance; Figure 4 It can be seen that a larger window value can be obtained by applying a small voltage of ±6V to the Au / S-MoTe2 / Au memristor device prepared by the present invention, which proves that sulfur doping can enhance its resistive switching performance.

[0074] from Figure 5 It can be seen that the Au / S-MoTe2 / Au memristor device prepared by the present invention is subjected to 6 IV cycles, and the device exhibits good simulated resistive switching performance; when the reading voltage is 0.2V and the test voltage is 2V ( Figure 6 ), the device shows the characteristic of gradually increasing current as time goes by, which also shows that the Au / S-MoTe2 / Au memristor device of the present invention has good resistance switching performance; Figure 7 It can be seen that when the reading voltage is 0.2V and the test voltage is -2V, the current of the Au / S-MoTe2 / Au memristor device of the present invention gradually weakens with the increase of time, showing an inhibitory characteristic, indicating that it has good resistive switching performance, laying the foundation for subsequent neuromorphic applications.

[0075] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.

Claims

1. A method for preparing sulfur-doped molybdenum ditelluride nanosheets, characterized in that: The following steps are involved: (1) Mixing the catalyst and the molybdenum source and placing them in an ark, and then placing the substrate on top of the ark to obtain a pretreated molybdenum source; (2) placing a tellurium source in the ark, and then placing the tellurium source and the pretreated molybdenum source in a double-temperature zone tubular furnace, with the tellurium source placed upstream and the pretreated molybdenum source placed downstream for growth reaction and heat preservation, to obtain molybdenum ditelluride nanosheets; (3) Soaking the molybdenum ditelluride nanosheets in an ammonium sulfide solution, taking them out, washing them with water, and drying them to obtain sulfur-doped molybdenum ditelluride nanosheets.

2. The method for preparing sulfur-doped molybdenum ditelluride nanosheets according to claim 1, characterized in that: The catalyst is sodium chloride or potassium chloride; the substrate is a SiO2 / Si substrate; the molybdenum source is molybdenum trioxide; and the tellurium source is tellurium powder.

3. The method for preparing sulfur-doped molybdenum ditelluride nanosheets according to claim 1 or 2, characterized in that: The mass ratio of the tellurium source to the molybdenum source is 1:0.04-0.

06.

4. The method for preparing sulfur-doped molybdenum ditelluride nanosheets according to claim 1, characterized in that: The carrier gas used in the double-temperature zone tubular furnace in step (2) is a mixture of argon and hydrogen; the volume concentration of the argon is 88-92%, and the volume concentration of the hydrogen is 8-12%; the carrier gas flow rate is 18-22 sccm.

5. The method for preparing sulfur-doped molybdenum ditelluride nanosheets according to claim 1, characterized in that: In the step (2), the heating temperature of the tellurium source is 550-650°C; the heating temperature of the pretreated molybdenum source is 650-750°C; the growth reaction time is 30-40 minutes; and the insulation time is 15-25 minutes.

6. The method for preparing sulfur-doped molybdenum ditelluride nanosheets according to claim 1, characterized in that: The mass percentage concentration of the ammonium sulfide solution in step (3) is 18-22%, and the soaking time is 10-20 minutes; the drying temperature is 45-55° C., and the drying time is 1.5-2.5 minutes.

7. Sulfur-doped molybdenum ditelluride nanosheets prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the sulfur-doped molybdenum ditelluride nanosheets according to claim 7 in preparing a memristor device.

9. The use according to claim 8, characterized in that The following steps are involved: The sulfur-doped molybdenum ditelluride nanosheets are placed on a coating machine, and 1 to 2 drops of photoresist are added to the surface of the substrate, and the coating is performed twice, and the substrate is dried for use; a photolithography machine is used to perform photolithography, exposure and development on both ends of the sulfur-doped molybdenum ditelluride nanosheets, and the nanosheets are taken out and dried; the dried sulfur-doped molybdenum ditelluride nanosheets are placed on the stage of a sputtering instrument and the height of the stage is adjusted, and a high-purity Au target is used for sputtering 2 to 3 times, each time for 15 to 20 seconds; the nanosheets are then soaked in acetone for 8 to 10 minutes, washed with water, ultrasonicated, and dried to obtain an Au / S-MoTe2 / Au memristor device.

10. The use according to claim 9, characterized in that The two times of coating include the following steps: coating at 400-600 r / min for 5-15 s, and then coating at 1800-2200 r / min for 25-35 s; the exposure time is 10-20 s; and the development time is 0.5-1.5 min.

Citation Information

Cited By

  • Semi-metal MoTe2 modification method and photoelectric detector based on modified semi-metal MoTe2

    CN120583769A

  • Methods for modifying MoTe2 semimetal and photodetectors based on modified MoTe2 semimetal

    CN120583769B